The Effectiveness of Watching Bareng in Realizing Religious Moderation (Studi Kasus Desa Saptorenggo, Kecamatan Pakis, Kabupaten Malang) - Nurunnisak, Khoyruna; Yuliasavitri, Najlazalfa; Fitriyah, Ainul; Umam, M. Najikhul; Saputra, M. Fladimir Ramang (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2024)
Indonesia is a plural country with many differences, one of which is the difference in religion and social affairs. A way is needed in order to realize religious and social harmony in society, namely through religious moderation. Religious moderation in Saptorenggo Village is carried out by watching together activities which coincide on New Year's Eve. The implementation of activities is carried out through several stages, namely field studies, activity design and activity execution. From some of these processes, the results show that the people of Saptorenggo Village already have a strong spirit of religious moderation, namely by instilling their beliefs by not blaming other beliefs. However, the majority of people are less tolerant of the celebration of the Christian New Year because it is considered not their religious New Year. The screening of the film entitled Memorizing the Delisa Prayer was attended by 30% of the people of Saptorenggo Village. The existence of watching together activities has resulted in the community starting to pave the way for developing religious moderation in people's social life.